An Analysis of Connotative Meaning in Joko Pinurbo's Poetry - Lisa Rahmawati; Muhid, Abdul; Miswaty, Titik Ceriyani (CV Insan Kreasi Media, 2022)
This study discusses the connotative meaning contained in the poetry by Joko Pinurbo. This study uses the theory of Leech (1981) and Palmer (1976) about connotative meaning and aspects of meaning. In the research method, the data were analyzed based on the definition of the qualitative descriptive method. The poetries of Joko Pinurbo were analyzed from each word and couplet. Then, each word and couplet in Joko Pinurbo's poetries were classified as connotative meaning and found the connotative word's aspect meaning. After analyzing, the researcher explained the data found and concluded this research. As the result, there are 13 connotative words found in this research. Of the four aspects of meaning that have been mentioned in chapter two of Joko Pinurbo's poetries, the researcher found two kinds of aspects of the meaning namely, nine the aspect of the meaning of feeling and four the aspect of the meaning of intension.